2011
DOI: 10.1111/j.1600-0579.2010.00656.x
|View full text |Cite
|
Sign up to set email alerts
|

Student self-confidence in coping with uncooperative behaviours in paediatric dentistry

Abstract: During paediatric dental treatment, non-collaboration and fearful reactions are frequently observed in the child client. The dentistry student must be prepared to cope with these reactions, particularly considering the importance of the relationship between dentists and patients in the promotion of oral health. The present study aimed to assess undergraduate dentistry students' perceptions of their ability to cope with non-collaboration situations in paediatric dentistry. A Likert-style questionnaire was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 10 publications
0
9
1
1
Order By: Relevance
“…It may improve student self-confidence and their ability to deal with hard situations [3]. A recent study showed that predoctoral students did not feel confident to treat children [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may improve student self-confidence and their ability to deal with hard situations [3]. A recent study showed that predoctoral students did not feel confident to treat children [26].…”
Section: Discussionmentioning
confidence: 99%
“…To be successful in pediatric dental treatment, it is necessary to choose adequate strategies, based on procedures that stimulate children's cooperative behavior, knowledge which should have been acquired during formal dentistry training [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Batista et al 45 avaliaram a percepção de estudantes de graduação em Odontologia sobre sua capacidade de enfrentar situações de não colaboração na área de Odontopediatria. Um questionário do modelo Likert foi usado para analisar os níveis de autoconfiança dos alunos e soluções propostas para 10 situações-problema que os alunos provavelmente encontrariam na vida profissional.…”
Section: Resultados E Discussão O Relações Comunidade-instituiçãounclassified
“…Psychological variables (anxiety and/or stress), sociocultural (individual characteristics, children"s maturity, previous dental experience), and legal requirements (parent"s consent) are involved in dental treatment interfering with professional performance [4]. To be successful in pediatric dental treatment, it is necessary to choose adequate strategies based on procedures that stimulate children"s cooperative behavior and knowledge which should have been acquired during formal dentistry training [5]. Apart from these techniques, behavioural management strategies start as soon as the patient arrives in the dental operatory, and also involve attire, voice tone, facial expression, body language, sense of humour of the dentist.…”
Section: Introductionmentioning
confidence: 99%